Asking For Forgiveness. A Proposed Solution for an Aporia in Hannah Arendt on Forgiveness and the Banality of Evil - de Arteaga Gallinal, Santiago (Tópicos, Revista de Filosofía, 2023)
The article offers a solution to an aporia present in Hannah Arendt concerning the banality of evil and forgiveness. The banality of evil implies the abandonment of thought by an agent and the negation of personhood; thus, it can be stated that, in fact, there is nobody to be found in a particular action. The problem is that, for Arendt, the meaning of forgiveness is that it is directed at the redemption of the person from her past. Then, the aporia of the banality of evil and forgiveness is that there is nobody to forgive. The structural-phenomenological condition for the appearance of the person is the request for forgiveness, for it is only this that manifests the reconstitution of the person through thought and reopens the space of appearance that makes the emergence of forgiveness possible.
Keywords: banality of evil; thinking; forgiveness; person